2021
DOI: 10.3389/fchem.2021.637730
|View full text |Cite
|
Sign up to set email alerts
|

The Abnormal Glycopatterns of Salivary Glycoproteins in Esophageal Squamous Cell Carcinoma Patients

Abstract: Glycosylation is one of the most crucial posttranslational modifications of proteins, containing a remarkable amount of biological information. The alteration of glycosylation is closely associated with certain diseases. Exploring glyco-code in the development of diseases is a hot topic in recent years. Esophageal squamous cell carcinoma (ESCC) is the primary pathological histology in developing countries and a severe threat to human health. Although the glycan profiles in the blood samples of ESCC patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Similar to our previous reports [25,26], the N-glycans of the isolated NAs were released by PNGase F glycosidase. The purified N-glycans of NA were characterized by MALDI-TOF/TOF-MS (Ultra eXtreme, Bruker Daltonics; Bremen, Germany) as described previously.…”
Section: Characterization Of N-glycan Profiles Of Nas By Maldi-tof/to...supporting
confidence: 88%
“…Similar to our previous reports [25,26], the N-glycans of the isolated NAs were released by PNGase F glycosidase. The purified N-glycans of NA were characterized by MALDI-TOF/TOF-MS (Ultra eXtreme, Bruker Daltonics; Bremen, Germany) as described previously.…”
Section: Characterization Of N-glycan Profiles Of Nas By Maldi-tof/to...supporting
confidence: 88%
“…A better understanding of each cellular condition is needed for advancing research on regenerative therapy due to differences in the various factors, including diseases and ages. In addition, further analysis of glycan composition via methods such as mass spectrometry will enhance understanding when combined with analysis of glycan structures, including branching, coordination, and binding modes (Shu et al 2021 ). Investigating optimal cellular ratios for remodeling and the carrier proteins of characteristic glycans will be important in making these glycans useful as indicators for clarifying the details of personalized cardiovascular conditions and cellular functions in patients.…”
Section: Discussionmentioning
confidence: 99%
“…N-linked glycoproteomic profiling analysis indicated that the expression of total procathepsin D and high-mannose procathepsin D was upregulated, while the expression of total haptoglobin, high-mannose clusterin and the GlcNAc/sialic acid-containing fraction of 14-3-3ζ was downregulated in ESCC tissues[ 91 ]. In addition, Shu et al [ 92 ] reported that the proportion of ESCC patients with GlcNAc or Galβ1-4GlcNAc-containing N-glycans was increased. Similarly, the expression of glycosylated proteins was distinct between the saliva of ESCC patients and that of healthy controls, and screening for ESCC biomarkers in saliva is noninvasive and may be a more acceptable approach[ 92 ].…”
Section: Screening and Early Diagnosis Of Esccmentioning
confidence: 99%
“…In addition, Shu et al [ 92 ] reported that the proportion of ESCC patients with GlcNAc or Galβ1-4GlcNAc-containing N-glycans was increased. Similarly, the expression of glycosylated proteins was distinct between the saliva of ESCC patients and that of healthy controls, and screening for ESCC biomarkers in saliva is noninvasive and may be a more acceptable approach[ 92 ]. In addition to screening and early diagnosis, glycosylated proteins may also be associated with the metastasis and prognosis of ESCC.…”
Section: Screening and Early Diagnosis Of Esccmentioning
confidence: 99%